Event-specific somatotype and physical characteristics of male and female elite alpine skiers - Aerenhouts, D.; Clijsen, R.; Fässler, R.; Clarys, P.; Taeymans, J. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Specific physical characteristics may be required for optimal performance in the different alpine skiing events varying in speed, duration and turning frequency. This ongoing study aims to describe the specific somatotype and physical characteristics in Slalom (SL) versus super-G and downhill (SG&DH) World Cup (WC) and Europa Cup (EC) male and female alpine skiers.